2013
DOI: 10.1021/ie4028878
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nanofibrillated Cellulose as a Rheology Modifier Additive in CMC-Containing Pigment-Coating Formulations

Abstract: Suspension rheology of aqueous coatings influences the coating application performance at high speeds and during high rates of change of the shear rate, as well as the quality of the coated end product determined by the relationship between dewatering, immobilization, and coating coverage. In the case of paper coatings, the end-use printing can be significantly affected by the coating uniformity, pore structure, and surface chemistry. Nanocellulose-containing materials, such as microfibrillated (MFC) and nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 44 publications
(126 reference statements)
3
89
0
1
Order By: Relevance
“…Initially, samples were subjected to low shear rate (0.1 s -1 ), then subsequently high shear rate (500 s -1 ), and finally once again low shear rate, the recovery stage (0.1 s -1 ). Structure recovery was traced in respect to recovery of dynamic transient viscosity (η + ) in the third interval, expressed as percentage (%) of ratio η + / η0 after 300 s of measurements, where η0 is the low shear viscosity at the beginning of first interval (Dimic-Misic et al 2013a).…”
Section: Itt (3 Interval Thixotropy Test) Recovery Measurementsmentioning
confidence: 99%
“…Initially, samples were subjected to low shear rate (0.1 s -1 ), then subsequently high shear rate (500 s -1 ), and finally once again low shear rate, the recovery stage (0.1 s -1 ). Structure recovery was traced in respect to recovery of dynamic transient viscosity (η + ) in the third interval, expressed as percentage (%) of ratio η + / η0 after 300 s of measurements, where η0 is the low shear viscosity at the beginning of first interval (Dimic-Misic et al 2013a).…”
Section: Itt (3 Interval Thixotropy Test) Recovery Measurementsmentioning
confidence: 99%
“…CNF is commonly prepared via mechanical disintegration of wood fibers, leading to fibril diameter as small as few nanometers and several micrometers in length [13]. They have been extensively suggested as strength promoters [14][15][16][17] and rheology modifiers [18]. CNF is also considered as an excellent shape anisotropic nanomaterial that is able to stabilize surfactant-free emulsions, also known as Pickering emulsions, via particle assembling and network formation at the interface [19,45].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed the pseudoplasticity and shear thinning behavior of NFC suspensions may improve the rheological properties of the coating material; as a result, the properties of coated paper may improve as well (Koepenick 2004(Koepenick , 2005. Researchers have used NFC as a rheology modifier additive in CMC-containing pigment coating formulations and found that NFC additives operated as a water-binding, gelforming component (Dimic-Misic et al 2013). In this work, it was also discovered that the substitution of CMC with NFC makes the introduction of new types of rheology modifiers in coating colors possible, which could lead to improved strength of coated paper.…”
Section: Introductionmentioning
confidence: 95%